Diverse echocardiographic changes in the course of hypoxia due to acute exacerbation of idiopathic pulmonary fibrosis - Toshimitsu Tsugu; Yuji Nagatomo; Hidefumi Koh; Kaoru Tanaka; Patrizio Lancellotti (KARE Publishing, 2020)
Idiopathic pulmonary fibrosis (IPF) is a progressive parenchymal disease. Pulmonary hypertension (PH) is a potentially lethal complication in the course of IPF. In almost all cases of IPF-PH there is gradual deterioration, but patients can also decline suddenly due to hypoxia. This case report describes the different echocardiographic changes observed in 2 episodes of hypoxic attack in a 73-year-old man. On admission, the tricuspid regurgitation peak gradient (TRPG) was 21 mmHg and the oxygen saturation rate was 94% (O2: 4 L/min). Five days after admission, the TRPG and oxygen saturation rate deteriorated [TRPG: 85 mmHg, oxygen saturation: 72% (O2; 4 L/min)]. He was diagnosed with IPF-PH due to hypoxic pulmonary vasoconstriction. Oxygen therapy and methylprednisolone pulse therapy (MPT) were administered. Five days after the MPT treatment, the hypoxia and PH improved [TRPG: 21 mmHg, oxygen saturation: 95% (O2: 4 L/min)]. Acute exacerbation of IPF (IPF-AE) occurred 20 days after the MPT, and a second dose of MPT was administered. The TRPG and oxygen saturation rate did not decline [TRPG: 27 mmHg, oxygen saturation: 94% (O2: 4 L/min)]. The patient died 10 days after the second dose of MPT. Divergent echocardiographic findings were observed during the deterioration of IPF-AE in the presence of IPF-PH.